Institutional context: What elements shape how community occupational therapists think about their clients' care?. (31st January 2020) - Carrier, Annie; Freeman, Andrew; Desrosiers, Johanne; Levasseur, Mélanie
Abstract: Clinical reasoning (CR) is the cognitive process that therapists use to plan, direct, perform and reflect on client care. Linked to intervention efficiency and quality, CR is a core competency that occurs within an institutional context (legal, regulatory, administrative and organisational elements). Because this context can shape how community therapists think about their clients' care, its involvement in their CR could have a major impact on the interventions delivered. However, little is known about this involvement. Our study thus aimed to describe the elements of the institutional context involved in community therapists' CR. From March 2012 to June 2014, we conducted an institutional ethnography (IE) inquiry in three Health and Social Services Centres in Québec (Canada). We observed participants and conducted semi‐structured interviews with 10 occupational therapists. We also interviewed 12 secondary key informants (colleagues and managers) and collected administrative documents ( n  = 50). We analysed data using the IE process. Of the 13 elements of the institutional context identified, we found that four are almost constantly involved in participants' CR. These four elements, that is, institutional procedures, organisation's basket of services, occupational therapists' mandate and wait times for their services, restrictively shape CR. Specifically, occupational therapists restrict their representation of the client's situation and exploration of potential solutions to what is possible within the bounds of these four elements. In light of such restrictions on the way they think about their clients' care, therapists should pay close attention to the elements of their own institutional context and how they are involved in their CR. Because of its potentially important impact on the future of professions (e.g. further restrictions on professionals' role, reduced contribution to population health and well‐being), this involvement of the institutional context in CR concerns all professionals, be they clinicians, educators, researchers or regulatory college officers.